1987
DOI: 10.1177/01454455870112001
|View full text |Cite
|
Sign up to set email alerts
|

Masculine Gender Role Stress

Abstract: It is proposed that masculine gender role socialization affects whether men appraise specific situations as stressful. Behavioral research on stress and coping has remained relatively blind to the possibility of significant gender role differences in appraising events as stressful. Therefore, a new scale was developed to measure masculine gender role stress (MGRS). Data were presented to substantiate hypotheses that MGRS scores (1) significantly distinguish men from women, (2) are unrelated to global measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
139
0
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(158 citation statements)
references
References 12 publications
5
139
0
14
Order By: Relevance
“…Our results indicated that an indirect relationship exists between the endorsement of traditional femininity ideology and anxiety, mediated through gender role stress. This was consistent with previous research that found feminine gender role stress to be associated with elevated levels of anxiety (Eisler and Skidmore 1988). These findings were also consistent with other research on gender, specifically on masculinity, which has shown that masculine gender role conflict correlates with anxiety among male college students (Davis 1997).…”
Section: Descriptive Statisticssupporting
confidence: 92%
“…Our results indicated that an indirect relationship exists between the endorsement of traditional femininity ideology and anxiety, mediated through gender role stress. This was consistent with previous research that found feminine gender role stress to be associated with elevated levels of anxiety (Eisler and Skidmore 1988). These findings were also consistent with other research on gender, specifically on masculinity, which has shown that masculine gender role conflict correlates with anxiety among male college students (Davis 1997).…”
Section: Descriptive Statisticssupporting
confidence: 92%
“…Guided by social constructionist perspectives on mas culinities, Wong, Shea and colleagues (2013) proposed the con struct subjective masculinity stress to refer to men's evaluations of stress associated with their phenomenological experiences of being male. Subjective masculinity stress can be distinguished from other stress-related masculinity constructs, such as gender role conflict (O'Neil, 2008) and masculine gender role stress (Eisler & Skidmore, 1987) that include predefined dimensions of masculin ities (e.g., restrictive emotionality, performance failure, and phys ical inadequacy). Instead of specifying dimensions of masculinities that are stressful for men, subjective masculinity stress is premised on the notion that men are actively engaged in relating their life experiences to their gender and that their evaluations of stress associated with such experiences can be highly idiosyncratic.…”
mentioning
confidence: 99%
“…To assess men's subjective masculinity stress, Wong, Shea et al (2013) developed a scale in which male respondents provide open-ended written statements about their personal experiences of what it means to be a man and then rate these experiences on the basis of how frequently they are stressful (see the Method section for a description). Wong, Shea et al (2013) argued that that this idiographic approach has the potential to capture stressful experi ences of masculinities that are more personally salient to men from diverse and subordinate backgrounds (e.g., male Asian interna tional students) relative to masculinity constructs and measures that focus on meanings of masculinities dominant in Western culture (e.g., Eisler & Skidmore, 1987). Previous research has demonstrated that men's subjective masculinity stress was posi tively related to psychological distress (Wong, Shea, et al, 2013) and that Asian international students' perceived racial discrimina tion was positively associated with indicators of psychological distress (Wang et al, 2013).…”
mentioning
confidence: 99%
“…Intemal consistency reliability for MGRS subscale scores have ranged from .68 to .84 (Fischer & Good, 1998;Moore et al, 2010). Eisler and Skidmore (1987) provided initial validity for the five-factor structure of the MGRS, and MGRS subscale scores have been associated with IPV behaviors (Moore et al, 2010), gender role confiict (Fischer & Good, 1998), and parental attachment (Fischer, 2007).…”
Section: Experiences In Close Relationships Scale-revised (Ecr-r; Framentioning
confidence: 97%
“…In particular, endorsing traditional roles rooted in hegemonic sexism over women has been associated with a variety of negative intrapersonal and interpersonal problems for men (see Levant & Richmond, 2007;Moore & Stuart, 2005, for reviews). One form of gender role strain, gender role stress, occurs when men rigidly adhere to traditional role norms to the point where violations cause psychological and physical distress (Eisler & Blalock, 1991;Eisler & Skidmore, 1987).…”
Section: Gender Role Strain Theorymentioning
confidence: 99%